MENGENAL KOMPLIKASI PENYAKIT DIABETES MELITUS MELALUI PEMANFAATAN FLASHCARDS ANATOMI TUBUH MANUSIA DI SMK AL-MUHADJIRIN DUA BEKASI - Fathan Nugrah Utama, Muhammad; Iswandani, Doni; Subagya, Guruh; Setiawan, Yayan; Elsha Shanty Fauzani, Dwi (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2026)
Diabetes Mellitus (DM) is a noncommunicable disease (NCD) with a steadily rising prevalence in Indonesia, influenced by genetic factors, lifestyle, and the public’s level of knowledge. The objective of this Community Service (PkM) activity is to improve adolescents’ knowledge of DM, its complications, and its treatment through the use of flashcards. The activity was conducted at SMK Al Muhadjirin 2 Bekasi on May 5, 2025, involving 26 tenth-grade students as participants. Education was provided through a workshop using flashcards, while evaluation was conducted using pre-test and post-test questionnaires. Data were analyzed using the Wilcoxon test to determine differences in knowledge levels before and after the intervention. The results showed a significance value of 0.072, indicating no significant difference in knowledge between the pre-test and post-test results. Although some participants showed an increase in scores, these changes were not statistically significant. Participant fatigue prior to the activity and a lack of seriousness in completing the questionnaires are suspected to have influenced the results. The conclusion is that the educational activity using flashcards was not effective in significantly improving students’ knowledge. Therefore, more interactive educational strategies and approaches tailored to the characteristics of the students are needed for future activities.